IMPLICATIONS FOR THE ENVIRONMENTAL-ENGINEERING COMPROMISE AS A RESULT OF THE AFTERMARKET OPTIMIZATION OF A DIESEL ENGINE - Manev, Nikola; Jovchevski, Igor; Dimitrovski, Dame; Nikolov, Elenior (Journal of Energy Technology, 2025)
New IC engines contain many systems that ensure better engine performance, while satisfying increasingly strict environmental norms and exhaust emission standards in what is known as an environmental-engineering compromise. However, controlling, calibrating, and subsequently optimizing high-performance engines in which the trade-offs between performance, economy and emissions take precedence, is a challenge for even the most experienced automotive engineers, as it includes major implications. With the rise of fuel prices however, in recent years, more and more transport companies and fleet owners have looked to improve their vehicles’ economy through different aftermarket optimizations of the vehicles` engines, rarely taking into account the impact of such changes on the overall balance imposed through the environmental-engineering compromise. This paper investigates the required changes into the engines` electronic control units to achieve higher power output and lower fuel consumption, while analyzing the benefits and shortcomings brought by these optimizations on the engines` short and long-term operation.